Investigating eukaryotic and prokaryotic diversity and functional potential in the cold and alkaline ikaite columns in Greenland - Thøgersen, Mariane Schmidt; Zervas, Athanasios; Stougaard, Peter; Ellegaard-Jensen, Lea (Frontiers in Microbiology, 2024)
The ikaite columns in the Ikka Fjord, SW Greenland, represent a permanently cold and alkaline environment known to contain a rich bacterial diversity. 16S and 18S rRNA gene amplicon and metagenomic sequencing was used to investigate the microbial diversity in the columns and for the first time, the eukaryotic and archaeal diversity in ikaite columns were analyzed. The results showed a rich prokaryotic diversity that varied across columns as well as within each column. Seven different archaeal phyla were documented in multiple locations inside the columns. The columns also contained a rich eukaryotic diversity with 27 phyla representing microalgae, protists, fungi, and small animals. Based on metagenomic sequencing, 25 highquality MAGs were assembled and analyzed for the presence of genes involved in cycling of nitrogen, sulfur, and phosphorous as well as genes encoding carbohydrate-active enzymes (CAZymes), showing a potentially very bioactive microbial community.